EMU's decentralized system of fiscal policy - Hagen, Jurgen von.; Wyplosz, Charles; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2008)
This paper reviews the macroeconomic use of national fiscal policy in EMU and examines the rational and scope for a collective insurance system which redistributes income among countries in response to asymmetric cyclical shocks. The analysis of the record of national fiscal policies before and after the adoption of the Maastricht Treaty finds evidence that the quality of fiscal policies has improved in two ways: they are more clearly countercyclical - or less procyclical - and they are more readily used to restore competitiveness than to attempt to boost demand when competitiveness is eroded. These observations suggest that fiscal policy remains a useful instrument. One question is whether it can be augmented - or perhaps substituted for - with a collective insurance system. Collective insurance is one alternative to external borrowing and lending and therefore one way to deal with the concerns that the SGP is meant to address. We examine in more detail two collective insurance systems: tax revenue sharing and unemployment insurance sharing. We find that the earlier is more promising and examine in some detail how it could be set up. It is no panacea, though. Any insurance mechanism entails moral hazard and that moral hazard can, at best, only be mitigated, not eliminated.
Economic Papers